An investigation into the Accuracy of Distance Measurements to an object with the Pulse (Non-Prism) Total Station - Ali, Sami Hamid (Sulaimani Journal for Engineering Sciences, 2016)
In order to achieve the results that meet the specifications of a given project, like engineering surveys (e. g., Surveying of Buildings) , the knowledge of the reliability and accuracy of the surveying equipment is inevitable. The reflectorless total stations are used nowadays for several applications in civil engineering work due to their highly accurate , easy and fast measurements in an automated measuring process. The present paper investigates the accuracy and limits for prismless instrument Total Station especially in relation to observations with large (horizontal and/or vertical) angle of incidence to the reflecting surface , its colours and types, and beam divergence of the measuring signal. This study has been carried out with various surveying field tests by prism and prismless modes, using the pulse (non-prism) TOPCON GPT-2006 Total Station to evaluate the limitations and accuracy of this instrument in surveying the buildings (distance measurements). The current study has confirmed that while observations at right angles to an object ( building) are generally well within manufacturer specifications (σ=±10 mm), observations to surfaces of a building from a position that is not at right angles to the surface of the building ( signal beam) can introduce errors. Also , this study suggests that the angle of incidence of the measuring signal to the building points ( external and internal corners and wall surface points) has a large influence on the accuracy of that measurement. It is recommended to use horizontal angle of incidence for measuring the detail survey points between (-36 to + 36) degrees from the normal. Also, in case of measurements to a vertical surface, the maximum measured vertical angles of incidence was about forty degrees when using prismatic observations and fifty degrees for reflector less measurements. Some surveying techniques and recommendations are suggested to overcome these problems. Moreover, a good understanding of the non-prism instrument is required to get the required accuracy of the project. When using other total station equipment, the results of the current study can be used as a general guide only. The results of the current practical field experiments, computations and analysis of these tests using various calculations and least squares theory and computer programs (Excel and AutoCAD 2010) are also presented in digital and/or graphical forms.
Keywords: Reflectorless Total Station; Accuracy Investigations; Surveying of Buildings; Angle of incidence; Reflecting Surfaces; Colours; Types of materials; Beam Divergence; Least squares Theory